Retrospective evaluation of osteosarcomas of the extremity in adults - Elkiran, Emin T.; Turker, Alev; Kars, Ayse; Harputluoglu, Hakan; Erman, Mustafa; Gedikoglu, Gokhan; Tekuzman, Gulten (Oxford Univ Press, 2006)
[Abstract Not Available]
31st Congress of the European-Society-for-Medical-Oncology -- SEP 29-OCT 03, 2006 -- Istanbul, TURKEY